Corporate Media Entrepreneurship in Public Service Broadcasts: An exploratory Study of IRIB use of External Innovations (2019)
In the age of Web 3.0 and abundance of user generated content, large media organizations are faced with the challenge of creativity. Their internal sources of creativity are limited and they face with many innovative ideas that are presented in social media freely and widely. For this reason, use of external sources of innovation is a key challenge for large media organizations, and particularly for public service media. This research addresses the challenge of IRIB, the Iranian public service broadcast, to acquire external sources of innovation. Theoretical framework of this research has been taken from the theory of efficient media markets, that proposes large organizations have advantage in resources, small enterprises on innovation, and facilitators on contracting. A series of interviews with selected IRIB managers conducted, and analysis of these data showed IRIB has no systematic approach to benefit from users’ innovation to address the problem of scarcity of creativity. Some practical suggestions have been provided for IRIB in particular, while several of them might be generalizable to some other large media firms. The findings of this research contributes to corporate media entrepreneurship and how it is fostered by Web 3.0 and social media